A percepção do aluno de Ciências Contábeis da Universidade Federal do Ceará relacionada ao código de ética profissional do contador - Andrade, Gabriel do Nascimento (2018)
The stubborn competition on the labor market strait the relationship between the professional accounting and the ethical norms. Because of several frauds, the competitiveness and the legislation turn into stricter about the ethical infringement, in the accounting sector. Recognize the accounting professional's importance, this research inquires the perception of the Accounting Science's students of the Federal University of Ceará about the knowledge level about Professional Ethical Code of Accounting. This is a descriptive research, using the survey method, and the collected data through questionnaires and treated qualitatively. That research met the purpose that was obtained when the following results: the students show a reasonable knowledge about the Professional Ethical Code of Accounting, agreeing with the fact of the majority consider the importance of the norm, and the fact that the discipline of General and Professional Ethics should remain obligatory in the university course. Even through the fact that they consider that this discipline deal satisfactorily way to subjects referring to the ethical-disciplinary norms inherent to the accounting professional.